Assessing Child Nutrient Intakes Using a Tablet-Based 24-Hour Recall Tool in Rural Zambia. (December 2015) - Caswell, Bess L.; Talegawkar, Sameera A.; Dyer, Brian; Siamusantu, Ward; Klemm, Rolf D. W.; Palmer, Amanda C.
Background: Detailed dietary intake data in low-income populations are needed for research and program evaluation. However, collection of such data by paper-based 24-hour recall imposes substantial demands for staff time and expertise, training, materials, and data entry. Objective: To describe our development and use of a tablet-based 24-hour recall tool for conducting dietary intake surveys in remote settings. Methods: We designed a 24-hour recall tool using Open Data Kit software on an Android tablet platform. The tool contains a list of local foods, questions on portion size, cooking method, ingredients, and food source and prompts to guide interviewers. We used this tool to interview caregivers on dietary intakes of children participating in an efficacy trial of provitamin A-biofortified maize conducted in Mkushi, a rural district in central Zambia. Participants were children aged 4 to 8 years not yet enrolled in school (n = 938). Dietary intake data were converted to nutrient intakes using local food composition and recipe tables. Results: We developed a tablet-based 24-hour recall tool and used it to collect dietary data among 928 children. The majority of foods consumed were maize, leafy vegetable, or small fish dishes. Median daily energy intake was 6416 kJ (1469 kcal). Conclusions: Food and nutrient intakes assessed using the tablet-based tool were consistent with those reported in prior research. The tool was easily used by interviewers without prior nutrition training or computing experience. Challenges remain to improve programming, but the tool is an innovation that enables efficient collection of 24-hour recall data in remote settings.